Brominated flame retardants in the indoor environment - Comparative study of indoor contamination from three countries - Venier, Marta; Audy, Ondřej; Vojta, Šimon; Bečanová, Jitka; Romanak, Kevin; Melymuk, Lisa; Krátká, Martina; Kukučka, Petr; Okeme, Joseph; Saini, Amandeep; Diamond, Miriam L; Klánová, Jana (Environment international, 2016)
Concentrations of more than 20 brominated flame retardants (FRs), including polybrominated diphenyl ethers (PBDEs) and emerging FRs, were measured in air, dust and window wipes from 63 homes in Canada, the Czech Republic and the United States in the spring and summer of 2013. Among the PBDEs, the highest concentrations were generally BDE-209 in all three matrices, followed by Penta-BDEs. Among alternative FRs, EHTBB and BEHTBP were detected at the highest concentrations. DBDPE was also a major alternative FR detected in dust and air. Bromobenzenes were detected at lower levels than PBDEs and other alternative FRs; among the bromobenzenes, HBB and PBEB were the most abundant compounds. In general, FR levels were highest in the US and lowest in the Czech Republic - a geographic trend that reflects the flame retardants' market. No statistically significant differences were detected between bedroom and living room FR concentrations in the same house (n=10), suggesting that sources of FRs are widespread indoors and mixing between rooms. The concentrations of FRs in air, dust, and window film were significantly correlated, especially for PBDEs. We found a significant relationship between the concentrations in dust and window film and in the gas phase for FRs with log KOA values <14, suggesting that equilibrium was reached for these but not compounds with log KOA values >14. This hypothesis was confirmed by a large discrepancy between values predicted using a partitioning model and the measured values for FRs with log KOA values >14.
Keywords: prach; halogenované difenylethery; Spojené státy americké; Dust; retardanty hoření; Brominated flame retardants; Window film; Environmental Monitoring; Halogenated Diphenyl Ethers; Flame Retardants; Housing; Indoor; Air Pollutants; United States; Air; látky znečišťující vzduch; monitorování životního prostředí; bydlení; Canada; Kanada; brombenzeny; Czech Republic; Air Pollution, Indoor; Česká republika; znečištění vzduchu ve vnitřním prostředí; Bromobenzenes